Fabrication of Polymer Light Guide Plate (LGP) using Direct CO2 Laser Structuring - Norfazilasari, Yasman; Raja Murfiqah, Raja Mohd Fouzy; Mohd Zairulnizam, Mohd Zawawi (Semarak Ilmu Publishing, 2024)
Light guide plates (LGPs) are an integral component that help distribute illumination from the light source in a variety of applications. Therefore, the design and quality of the microstructure pattern in LGPs play a significant role in achieving high luminous efficiency and light uniformity. This study investigates the relationship between laser power and laser scanning speed to the formation of micro-dots by using CO2 direct laser structuring on PMMA. Furthermore, the effect of different micro-dots pitch to the luminance was also evaluated using the luminance meter. Our finding shows that increase of laser power and decrease of laser scanning speed resulted in larger micro-dots diameter and deeper micro-dots. The results also showed that the smaller the pitch, the higher the luminance reading. Overall, the low-cost CO2 direct laser structuring demonstrated in the study able to produce consistent micro-dots pattern diameter and height which is suitable for fabrication of LGPs in the mass production.